2021
DOI: 10.2174/1389201021666200607185250
|View full text |Cite
|
Sign up to set email alerts
|

Oleamide in Ipomoea and Dillenia Species and Inflammatory Activity Investigated through Ion Channel Inhibition

Abstract: Background: Oleamide is an essential substance for human health. So, the plants with high oleamide content are great sources for health care products. Objective: This study is conducted to investigate the quality of oleamide in plants and test the bioactivity in the selected two studied species. Methods: The three Ipomoea and five Dillenia species including Ipomoea alba, Ipomoea aquatica and Ipomoea pes-caprae, and Dillenia indica, Dillenia obovata, Dillenia ovata, Dillenia parviflora and Dillenia pentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, the experiment on oleamide activity merits further study given its use for treatments of Alzheimer's disease, stress, deep sleep, and appetite induction [10]. Recently, the anti-inflammatory effect of oleamide has been shown [11][12][13]. Additionally, phytol was present at 21.58% in I. batatas, 13.35% in I. carnea, and 11.76% in I. pes-caprae; but the amount was not high enough to functionally support the bioactivities of the plants.…”
Section: Discussionmentioning
confidence: 99%
“…However, the experiment on oleamide activity merits further study given its use for treatments of Alzheimer's disease, stress, deep sleep, and appetite induction [10]. Recently, the anti-inflammatory effect of oleamide has been shown [11][12][13]. Additionally, phytol was present at 21.58% in I. batatas, 13.35% in I. carnea, and 11.76% in I. pes-caprae; but the amount was not high enough to functionally support the bioactivities of the plants.…”
Section: Discussionmentioning
confidence: 99%
“…Hachisu et al (2015) explained that oleamide is a protective agent against memory loss in Alzheimer's disease and can increase drowsiness cause deep sleep, increase appetite, and has no side effects on blood pressure, heart rate, and body temperature. According to Ameamsri et al (2021), oleamide exhibits anti-inflammatory effects and has been used in the prevention and treatment of various diseases such as atherosclerosis, arthritis, and cancer through its metabolic conversion activity. According to Falowo et al (2017), siloxane compounds are compounds that have high antioxidant activity and play an active role as anti-microbials.…”
Section: Secondary Metabolites Productionmentioning
confidence: 99%
“…It is found in green algae such as Chromochloris zofingiensis and in few terrestrial plants. There are numerous biological activities related to this compound [29][30][31]. In general, oleamide from green algae is used in the treatment/prevention of arthritis, atherosclerosis, thrombosis, and cancer [32].…”
Section: Identification Of Compounds By Gc-msmentioning
confidence: 99%
“…In general, oleamide from green algae is used in the treatment/prevention of arthritis, atherosclerosis, thrombosis, and cancer [32]. It was reported that oleamide from terrestrial plants (Ipomoea and Dillenia species) excretes anti-inflammatory properties [29]. Furthermore, oleamide from the fungus Colletotrichum gloeosporioides has confirmed antimicrobial activity against Staphylococcus aureus (zone of inhibition = 25 mm) [33].…”
Section: Identification Of Compounds By Gc-msmentioning
confidence: 99%